Impacts of Protein from High-Protein Rice on Gelatinization and Retrogradation Properties in High- and Low-Amylose Reconstituted Rice Flour - Yitong Zhao; Xianggui Dai; Enerand Mackon; Yafei Ma; Piqing Liu (Agronomy, 2022)
High-protein rice is nutritional, but its taste attributes are inferior to low-protein rice. Many documents correlate its taste attributes with its gelatinization and retrogradation properties. This study investigated the changes in gelatinization and retrogradation properties of low- and high-amylose reconstituted rice flour (RRF) added with different fractions of proteins extracted from high-protein rice. The addition of protein decreased the RVA (rapid viscosity analyzer) viscosity parameters of the RRF but increased the peak time. The high amylose fractions in the RRF mainly increased the parameters PV, FV, SB, and peak times, and scarcely affected the parameters BD and PaT. The interaction between amylose and protein determined the pasting temperature. Protein addition in RRF significantly decreased gelatinization enthalpies but increased the onset temperature (To) and peak temperature (Tp), while the amylose in RRF increased the gelatinization enthalpies, To and Tp. Protein additions decreased the gel hardness and the pore size, while the amylose increased the gel hardness but decreased pore size. Our findings may be potentially useful in breeding and cultivating high-protein rice.